Shaker Zahra Author Bibliometric Study - Analysis of Scientific Publications from 1985 until 2014 - Silva & Academic Board of Revista de Negócios, Arlan (Revista de Negócios, 2016)
The study is presented aims to demonstrate through a bibliometric study, analysis of academic, scientific and technical publications developed by Shaker Zahra between the years 1985-2014, representing 29 years of study.Â To enhance this objective, we sought inÂ theÂ first instance to a bibliographic description of bibliometrics, entrepreneurship and the relationship between them.Â After this, was demonstrated academic and professional history Zahra, describing their field.Â In sequence, it was presented the methodology of the study, which had focused its characterization longitudinal and quantitative research, which allowed the development of bibliometric analysis.Â The final part included the description of limitations and proposals for future studies, closing the research, with conclusions and references.Â The study was developed through the analysis of 160 scientific papers published by Shaker Zahra in partnership with other researchers in high-impact journals and academic and scientific importance were obtained at Portal Capes and Google Scholar Portal.